2019
DOI: 10.1038/s41598-019-53645-w
|View full text |Cite
|
Sign up to set email alerts
|

Differential Pattern of Soluble Immune Markers in Asymptomatic Dengue, West Nile and Zika Virus Infections

Abstract: Infections with dengue virus (DENV), West Nile virus (WNV) and Zika virus (ZIKV) usually present similar mild symptoms at early stages, and most infections (~80%) are asymptomatic. However, these infections may progress to severe disease with different clinical manifestations. In this study we attempted to identify unique characteristics for each infection at the presymptomatic/asymptomatic stage of infection and compared levels of soluble immune markers that have been shown to be altered during clinical cours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…Our results have also shown the presence of a similar set of cytokines including IFN-γ, IL-4, IL-10, and TNF-α in the serum of patients with WNV fever and WNND. Fares-Gusmao et al [ 13 ] investigated cytokines as a part of immune marker profiles in acute, viremic pre-symptomatic/asymptomatic blood donors subsequently diagnosed with flavivirus infections including dengue virus (DENV), WNV and Zika virus (ZIKV) as well as in controls. A comprehensive analysis of biological response modifiers in the plasma of WNV-infected blood donors showed increased concentrations of cytokines (IFN-γ, IL-1β, IL-2, IL-12, IL-17, IL-10, IL-4, and IL-5), soluble cytokine receptors (IL-2R and ST2/IL-1R4), granulocyte macrophage colony stimulating factor GM-CSF, and chemokines (CXCL8 and CXCL9), as well as decreased levels of several apoptosis-related molecules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results have also shown the presence of a similar set of cytokines including IFN-γ, IL-4, IL-10, and TNF-α in the serum of patients with WNV fever and WNND. Fares-Gusmao et al [ 13 ] investigated cytokines as a part of immune marker profiles in acute, viremic pre-symptomatic/asymptomatic blood donors subsequently diagnosed with flavivirus infections including dengue virus (DENV), WNV and Zika virus (ZIKV) as well as in controls. A comprehensive analysis of biological response modifiers in the plasma of WNV-infected blood donors showed increased concentrations of cytokines (IFN-γ, IL-1β, IL-2, IL-12, IL-17, IL-10, IL-4, and IL-5), soluble cytokine receptors (IL-2R and ST2/IL-1R4), granulocyte macrophage colony stimulating factor GM-CSF, and chemokines (CXCL8 and CXCL9), as well as decreased levels of several apoptosis-related molecules.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Fares-Gusmao et al [ 13 ] identified a common immune signature for asymptomatic infections with DENV, WNV and ZIKV that included increased levels of IL-12, IL-17, IL-5, IL-10, CXCL9, E-Selectin and ST2/IL-1R4 as well as decreased levels of IL-13 and CD40 when compared to controls. These results suggest that cytokines could be further evaluated as possible surrogate biomarkers for differentiation of early flavivirus infections before seroconversion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disparity between the number of reported cases and estimates of actual cases makes it tough to capture the true burden of these mosquito-borne diseases. Approximately 80% of individuals infected by DENV and ZIKV remain asymptomatic throughout the infection, presenting no symptoms or clinical signs of infection [4,[19][20][21][22], which lead to under-estimation and under-reporting by official passive surveillance and reporting systems. Seroprevalence studies, as a supplement for traditional symptom-based and laboratory-based surveillance, are essential for assessing the true disease burden of mosquito-borne diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, further studies showed that, in chronic infection of various liver cells, treatment with a PPARα antagonist, which also down-regulates hydroxymethylglutaryl-CoA (HMG-CoA) synthase gene, was able to reduce HCV replication and resulted in increased lipid and LD accumulation likely, at least in part, owing to the role exhibited by PPARα in lipid catabolism ( Rakic et al, 2006 ). Inhibition of the PPAR signaling pathway was also observed in DENG, and WNV-infected asymptomatic donors ( Fares-Gusmao et al, 2019 ). By contrast, a recent study from Al-Qahtani et al (2017) reported the induction of PPARγ in MERS-infected cells, which occurred after 24 h and not at earlier stages of stimulation.…”
Section: Peroxisome Proliferators Activated Receptors and Lipid Metabmentioning
confidence: 94%